Componente financiero del informe macro ambiental del departamento del Quindío vigencia 2012 (2013)
The financial component of Quindío Department environmental report for year 2012 have information about of the environmental investment done by the entities audited by Contraloría General of Quindío. These entities are: companies providing home services (water, cleanliness, sanitary landfill): Esaquin S.A, Esacor S.A., Cafeaseo del Quindío, and Multipropósito S.A; entities health service as San Juan de Dios Hospital (Armenia), Mental Hospital (Filandia), Pio X Hospital (La Tebaida) and Misericordia Hospital (Calarcá), the Government Departmental and the Quindio University. In addition, it`s possible to meet the allocation of economic resources for environmental projects, programs and actions; the environmental management done for these entities for reducing the environmental impact produced for human activities, preserving of natural resources and biodiversity and to comply the environmental laws of course their functions. The report shows the efectivity of internal control system of entities above environmental actions, and the outcomes of the environmental management.